Strontium mediated modification of structure and ionic conductivity in samarium doped ceria/sodium carbonate nanocomposites as electrolytes for LTSOFC. Issue 88 (7th September 2016) - Aarthi, U.; Arunkumar, P.; Sribalaji, M.; Keshri, Anup Kumar; Babu, K. Suresh
Abstract : Addition of strontium modifies the structure and interaction behaviour in ceria–sodium carbonate nanocomposites with respect to sintering temperature. Abstract : The structural changes on the addition of strontium in samarium doped ceria/Na2 CO3 nanocomposites were investigated with respect to sintering temperature. The nanocomposites prepared by a co-precipitation method in the presence (SrSDS) and absence (SDS) of strontium were sintered at 500, 600 and 700 °C. XRD results indicated an increase in crystallite size and lattice parameter with respect to sintering temperature in the presence of strontium. Raman, SEM and FT-IR studies confirmed the presence of Na2 CO3 and CeO2 phases. The observed changes in crystallinity and oxygen vacancy concentrations indicate the beneficial role of strontium upon sintering up to 600 °C. The impedance spectral analysis clearly shows the beneficial effect of adding strontium to the composite. The lowest activation energy (0.61 eV) with the highest conductivity (3.8 × 10 −3 S cm −1 ) for SrSDS sintered at 600 °C arises due to the strong interaction between the Na2 CO3 and CeO2 phase. However, sintering the composites at 700 °C indicated a negligible effect of strontium due to the decomposition of Na2 CO3, thereby limiting the operational temperature of the nanocomposites for potential fuel cell applications.